The alternative press in Namibia, 1960-1990 - Heuva, William Edward (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1996)
The study seeks to document the development of the alternative press in Namibia from 1960 to 1990. It traces the reasons for its emergence and outlines the stated aims and objectives in order to illustrate its attempts to nurture a culture - of colonial resistance. It is argued that structural factors such as funding, distribution, advertisements and ownership enabled the alternative press to operate outside the South African apartheid hegemony. The study explains how the intellectuals used the alternative press in their attempts to mobilise and organise colonised Namibians for social change. They did this by formulating and disseminating ideologically constructed discourses (messages) which challenged the colonial discourse. These messages were produced and directed towards a specific audience, the masses to whom the intellectuals were organically linked. Their primary news definers were also drawn from the ranks of these masses. It is further argued that the alternative press came to represent the colonised masses by voicing their needs and aspirations which were marginalised by the mainstream colonial media. Finally, a relatively detailed analysis of the content, the language used and the'messages carried by the alternative press has been made to demonstrate its political agenda, which was to empower the masses to achieve their objective - the attainment of political independence. These issues are analyzed against a background of theoretical frameworks which seek to explain how subordinated groups and classes in a state of domination sought to establish alternative channels of communication in the creation of a counter hegemonic order.
Keywords: Press -- Namibia; Press and politics -- Namibia; Namibia -- Newspapers